In defence of a political economy of the media - Meehan, Eileen R. (Javnost (Ljubljana), 2013)
This essay addresses recent misrepresentations of the study of political economy of the media. The discussion is grounded in some historical background, including a brief sketch of some of the history of critical communications research in the US, which flourished within the global profusion of critical research in the 1960s and 1970s. Part of this history isthe emergence of organisational support for critical scholarship as well as the long-term employment of individual scholars by specific universities that made critical classes part of both graduate and undergraduate curricula. That process of institutionalisation provided the basis for the next generations ofcritical scholars from the 1980s through the present - generations whose research address a broad range of communications phenomena, use a wide range of research methods, and draw from a wide array of critical theories. This overview sets the stage for a critique of the current attack on radical political economy specifically. That attack is considered in terms of two key texts that caricature political economic research as an enterprise dependent on theories imported from the Frankfurt School, limited to a macroscopic approach, only interested in journalism, and ignoring both media workers and media audiences.
Keywords: mass media; množični mediji; communication; komuniciranje; kriticizem